2020
DOI: 10.1080/01434632.2020.1839472
|View full text |Cite
|
Sign up to set email alerts
|

The promise and resilience of multilingualism: language ideologies and practices of Polish-speaking migrants in the UK post the Brexit vote

Abstract: This article aims to examine how sociopolitical changes impact language ideology and linguistic practices within transnational multilingual families with a particular focus on families with ties to Poland in post-EUreferendum Britain. Drawing on the survey and ethnographic interview data collected as part of the ESRC-funded Family Language Policy project between 2017 and 2019, we found that the public attitude towards Polish and Polish speakers have changed significantly following the Brexit vote. While genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…It is also worth mentioning that, in this study, the families’ language planning did not involve them limiting themselves to speaking a specific language with each other or their children, for example, in the form of the one-parent-one-language (Soler & Zabrodskaja, 2017) or only-the-heritage-language-at-home approaches (Hua & Wei, 2016) that many studies have found families subscribing to. Worries about proficiency (e.g., Yue and her desire to improve her Turkish), likewise, did not hinder the parents’ use of multiple languages when interacting with each other, in contrast to the findings from other studies (e.g., Kozminska & Hua, 2021). The free use of languages and their emphasis on seeing languages as interchangeable may have stemmed from the participants seeing a reduced distance between the languages in their repertoires as a result of being multilingual (Benet-Martínez & Haritatos, 2005), similar to some of the US-European couples in the study by Piller (2002).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…It is also worth mentioning that, in this study, the families’ language planning did not involve them limiting themselves to speaking a specific language with each other or their children, for example, in the form of the one-parent-one-language (Soler & Zabrodskaja, 2017) or only-the-heritage-language-at-home approaches (Hua & Wei, 2016) that many studies have found families subscribing to. Worries about proficiency (e.g., Yue and her desire to improve her Turkish), likewise, did not hinder the parents’ use of multiple languages when interacting with each other, in contrast to the findings from other studies (e.g., Kozminska & Hua, 2021). The free use of languages and their emphasis on seeing languages as interchangeable may have stemmed from the participants seeing a reduced distance between the languages in their repertoires as a result of being multilingual (Benet-Martínez & Haritatos, 2005), similar to some of the US-European couples in the study by Piller (2002).…”
Section: Discussioncontrasting
confidence: 60%
“…Studies like those conducted by Tannenbaum (2012) and Tannenbaum and Yitzhaki (2016) are exceptions in this respect because they expand on the language planning concept to focus not only on particular languages but on how certain families use their languages as an emotional response to sociopolitical conditions or as a defense mechanism. Yet, even in these studies, like in most others (e.g., Kwon, 2020; Oriyama, 2016; for an extensive review of FLP studies involving TMFs, see Duff, 2015; Gomes, 2018; Hirsch & Lee, 2018; Lanza & Lexander, 2019), the participating families tend to be monoethnic and even functionally monolingual (at least with each other), and the findings concern the speaking of one or another language without a deeper engagement with the participants’ multilingualism (see Kozminska & Hua, 2021). For instance, in the study by Tannenbaum and Yitzhaki (2016, pp.…”
Section: Multilingualism and Language Planningmentioning
confidence: 86%
“…Notable exceptions to this are the handful of studies that have addressed how Brexit was experienced in the context of EU families and intimate relations (see, for example, Allen and Ögtem-Young, 2020; Brahic, 2020; Kozminska and Zhu, 2021; Sigona and Godin, 2019b). For example, drawing on research across the UK, Nando Sigona and Marie Godin (2023) highlighted the situated politics of Brexit on EU families.…”
Section: Families Citizens’ Rights and Brexitmentioning
confidence: 99%